PENERAPAN TERAPI AIUEO PADA PASIEN STROKE UNTUK MENINGKATKAN KEMAMPUAN BICARA : STUDI KASUS - Rahmi, Hani Aisya; Permana, Ryan Hara (LPPM Institut Pendidikan Nusantara Global, 2024)
In the elderly, there are many diseases that can easily attack, one of which is stroke. Strokes can occur due to several risk factors and the physiological function of the elderly which naturally declines. One of the impacts of a stroke is a decrease in speaking ability, therefore AIUEO speech therapy intervention can be given as a therapy to improve speaking ability. The aim of this research was to see the improvement in speaking ability of Mr. A with stroke through the implementation of AIUEO speech therapy interventions. This research uses a case study method with one respondent, data collection is carried out by observation and interviews. The intervention provided is AIUEO speech therapy. The instrument used is the FAST assessment format. The data analysis carried out was data reduction, presentation and conclusions. The results of the nursing evaluation after nursing actions were carried out for four days showed that there was an increase in the client's speaking ability. It is hoped that the results of this study will be useful as a reference for developing standard operating procedures or SOP.